“Supersessionism”: The Political Origin of a Theological Neologism - Azar, Michael G. (Studies in Christian-Jewish Relations, 2022)
This article proceeds along three primary lines. First, through an examination of the writings of Roy and Alice Eckardt and Franklin Littell, it demonstrates that the categorizing of ancient and modern Christian thinkers under the umbrella of “supersessionism” (along with the label for its proponent, the “supersessionist”) originated not in scholarly works of theological history or systematic theology, where the concepts now most frequently appear, but in the political environment of burgeoning American Christian support for the State of Israel’s military superiority. Second, this article foregrounds the way that these writings opposed themselves to Eastern Christians, Arabs, and church fathers. Third, it shows that, in light of their approach to both “traditional” theology and Christian (especially Orthodox) and non-Christian Arabs, the Eckardts, Littell, and other likeminded pioneers of American Christian-Jewish relations did not so much overcome the “supersessionism” myth that they identified and rejected as much as they redirected its principal elements toward a new cast of characters. The article concludes by briefly considering the common role played by “supersessionism” as a sort of “gateway” into Jewish-Christian relations for non-Western theologians, with the hope of reshaping a historically problematic aspect of Jewish-Christian relations that has tended to hinder, rather than facilitate, more frequent Orthodox and other Arab Christian participation in Jewish-Christian dialogue.